Responsiveness of clinical and ultrasound outcome measures in musculoskeletal systemic lupus erythematosus. (3rd January 2019) - Mahmoud, Khaled; Zayat, Ahmed S; Yusof, Yuzaiful; Hensor, Elizabeth; Conaghan, Philip G; Emery, Paul; Vital, Edward M
Abstract: Objective: To assess the responsiveness of clinical outcome measures in musculoskeletal SLE compared with US. Methods: A prospective pilot study was conducted in consecutive SLE patients with inflammatory musculoskeletal symptoms. Clinical assessments including SLEDAI, BILAG, 28 tender and swollen joint counts, physician and patient visual analogue scales (VAS), and US were performed at 0, 2 and 4 weeks following 120 mg i.m. methylprednisolone acetate. Responsiveness was analysed using changes and effect sizes using Cohen's criteria. Results: Twenty patients were recruited. Fifteen out of 20 had clinical swelling at baseline. All clinical and US parameters were significantly improved at week 4 (all P ⩽ 0.01). Musculoskeletal-BILAG score improved in 16/20. Musculoskeletal-SLEDAI improved in 7/20. SLE responder index 4 criteria were assessed in 19 patients with SLEDAI ⩾4 at baseline and were met in 9/19 at 4 weeks. Effect sizes at 4 weeks were large (>0.5) for US, physician VAS and BILAG, and medium (>0.3) for joint counts and SLEDAI. Large effect sizes for improvement in US grey-scale and power Doppler were observed in both SLE responder index 4 responders ( r = −0.51 and −0.56, respectively) and non-responders ( r = −0.62 and −0.59, respectively) at 4 weeks. Conclusion: This is the first study to measure the responsiveness of clinical outcome measures in musculoskeletal SLE against an objective inflammation measure. BILAG and physician VAS were the most responsive clinical instruments. US was highly responsive in musculoskeletal SLE, while SLEDAI and joint counts appeared suboptimal for detection of improvement. These results suggest that clinical trials based on the SLEDAI and SLE responder index 4 may underestimate the efficacy of therapy in SLE.